Fitness Cost of Fluoroquinolone Resistance in Clinical Isolates of Pseudomonas aeruginosa Differs by Type III Secretion Genotype - Agnello, Melissa; Finkel, Steven E.; Wong-Beringer, Annie (Frontiers in Microbiology, 2016)
Fluoroquinolone (FQ) resistance is highly prevalent among clinical strains of Pseudomonas aeruginosa, limiting treatment options. We have reported previously that highly virulent strains containing the exoU gene of the type III secretion system are more likely to be FQ-resistant than strains containing the exoS gene, as well as more likely to acquire resistance-conferring mutations in gyrA/B and parC/E. We hypothesize that FQ-resistance imposes a lower fitness cost on exoU compared to exoS strains, thus allowing for better adaptation to the FQ-rich clinical environment. We created isogenic mutants containing a common FQ-resistance conferring point mutation in parC from 3 exoU and 3 exoS clinical isolates and tested fitness in vitro using head-to-head competition assays. The mutation differentially affected fitness in the exoU and exoS strains tested. While the addition of the parC mutation dramatically increased fitness in one of the exoU strains leaving the other two unaffected, all three exoS strains displayed a general decrease in fitness. In addition, we found that exoU strains may be able to compensate for the fitness costs associated with the mutation through better regulation of supercoiling compared to the exoS strains. These results may provide a biological explanation for the observed predominance of the virulent exoU genotype in FQ-resistant clinical subpopulations and represent the first investigation into potential differences in fitness costs of FQ-resistance that are linked to the virulence genotype of P. aeruginosa. Understanding the fitness costs of antibiotic resistance and possibilities of compensation for these costs is essential for the rational development of strategies to combat the problem of antibiotic resistance.